The definition of medicine: A transition from discipline to transdisciplinarity to promote health in contemporary times (Ágora de Heterodoxias, 2025)
The definition of medicine has evolved throughout history, shifting from a body-centered perspective to a broader conception that encompasses the human being as a whole. This essay seeks to explore the definition of medicine from a transdisciplinary perspective. Contemporary medicine acknowledges the importance of mental and social health, in addition to physical health. This discipline intersects with various fields of knowledge, such as philosophy and sociology, and continuously faces constant challenges posed by technological advancements. Medical ethics plays a critical role in both clinical practice and decision-making.
Keywords: Medicine; Transdisciplinarity; Medical Anthropology; Definition of Medicine